Factors Associated with Lower Extremity Dysmorphia Caused by Lower Extremity Lymphoedema. (July 2017) - Yamamoto, T.; Yamamoto, N.; Yoshimatsu, H.; Narushima, M.; Koshima, I.
Abstract : Objectives: Indocyanine green (ICG) lymphography has been reported to be useful for the early diagnosis of lymphoedema. However, no study has reported the usefulness of ICG lymphography for evaluation of lymphoedema with lower extremity dysmorphia (LED). This study aimed to elucidate independent factors associated with LED in secondary lower extremity lymphoedema (LEL) patients. Methods: This was a retrospective observational study of 268 legs of 134 secondary LEL patients. The medical charts were reviewed to obtain data of clinical demographics and ICG lymphography based severity stage (leg dermal backflow [LDB] stage). LED was defined as a leg with a LEL index of 250 or higher. Logistic regression analysis was used to identify independent factors associated with LED. Results: LED was observed in 106 legs (39.6%). Multivariate analysis revealed that independent factors associated with LED were higher LDB stages compared with LDB stage 0 (LDB stage III; OR 17.586; 95% CI 2.055–150.482; p  = .009) (LDB stage IV; OR 76.794; 95% CI 8.132–725.199; p  < .001) (LDB stage V; OR 47.423; 95% CI 3.704–607.192; p  = .003). On the other hand, inverse associations were observed in higher age (65 years or older; OR 0.409; 95% CI 0.190–0.881; p  = .022) and higher body mass index (25 kg/m 2 or higher; OR 0.408; 95% CI 0.176–0.946; p  = .037). Conclusions: Independent factors associated with LED were elucidated. ICG lymphography based severity stage showed the strongest association with LED, and was useful for evaluation of progressed LEL with LED.